2014
DOI: 10.1186/bcr3693
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-18a inhibits hypoxia-inducible factor 1α activity and lung metastasis in basal breast cancers

Abstract: IntroductionIn breast cancer, distinct expression profiles of microRNAs (miRNAs) have been associated with molecular subgroups and clinicopathological characteristics, implicating a diagnostic and prognostic role of miRNAs. However, the biological functions of deregulated miRNAs in tumor progression are not yet completely defined. In this study, we investigated the function of miR-18a in regulating breast cancer metastasis through the hypoxia-inducible factor 1α (HIF1A)–dependent hypoxic response.MethodsAn ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 50 publications
6
64
0
1
Order By: Relevance
“…MiR-18a functions as a tumor suppressor to suppress cell proliferation by targeting Dicer in bladder cancer T24 cells [30]. Ectopic expression of miR-18a in a metastatic variant of MDA-MB231 cells reduced primary tumor growth and lung metastasis in basal breast cancers through a HIF1A-dependent pathway [31]. And ectopic expression of miR-18a significantly diminished cell proliferation in SGC-7901 cells, causing a marked reduction in tumor angiogenesis assessed by CD31-stained microvessel count [14].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-18a functions as a tumor suppressor to suppress cell proliferation by targeting Dicer in bladder cancer T24 cells [30]. Ectopic expression of miR-18a in a metastatic variant of MDA-MB231 cells reduced primary tumor growth and lung metastasis in basal breast cancers through a HIF1A-dependent pathway [31]. And ectopic expression of miR-18a significantly diminished cell proliferation in SGC-7901 cells, causing a marked reduction in tumor angiogenesis assessed by CD31-stained microvessel count [14].…”
Section: Discussionmentioning
confidence: 99%
“…miR-18a may directly target ER (28,29) and suppress hypoxia-inducible factor 1a activity (30) and ATM expression (31,32). The expression of miR-18a was at higher levels in ER-negative tumors than in ERpositive tumors (20,27).…”
Section: Er-bbb Casementioning
confidence: 99%
“…Increasing evidences indicated that some miRNAs act as either tumor suppressors or promoters in the development of various cancers and play crucial roles in causing messenger RNA (mRNA) degradation or translational inhibition by interacting with the 3′-untranslated region (3′-UTR) of the target mRNA [2][3][4]. Treatment by targeting microRNAs (miRNAs) has attracted extensive research attention in various cancers, including breast cancer [5][6][7][8]. However, the molecular underpinnings of cell proliferation and cell cycle in breast cancer remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%